2015
DOI: 10.1002/etc.3053
|View full text |Cite
|
Sign up to set email alerts
|

Biopesticide‐induced behavioral and morphological alterations in the stingless bee Melipona quadrifasciata

Abstract: Because of their natural origin, biopesticides are assumed to be less harmful to beneficial insects, including bees, and therefore their use has been widely encouraged for crop protection. There is little evidence, however, to support this ingrained notion of biopesticide safety to pollinators. Because larval exposure is still largely unexplored in ecotoxicology and risk assessment on bees, an investigation was performed on the lethal and sublethal effects of a diet treated with 2 bioinsecticides, azadirachtin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
0
6

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 61 publications
(48 citation statements)
references
References 58 publications
1
39
0
6
Order By: Relevance
“…Azadirachtin was reported to be able to impair development of the reproductive system in several insect species, including Partamona helleri queens, Tuta absoluta , and Drosophila melanogaster . Moreover, azadirachtin‐induced imbalance in the titer of ecdysteroid and juvenile hormone could make great contributions to the abnormal development in reproductive system and have influences on reproduction via impairment of oogenesis and vitellogenesis, reducing mating probability and motility . In this study, the effect of azadirachtin on the reproduction in male S.litura was recorded, and iTRAQ combined with molecular evidence was applied to isolate the azadirachtin‐responsive proteins in male reproductive organ of S.litura to uncover the detailed mechanism.…”
Section: Discussionmentioning
confidence: 83%
“…Azadirachtin was reported to be able to impair development of the reproductive system in several insect species, including Partamona helleri queens, Tuta absoluta , and Drosophila melanogaster . Moreover, azadirachtin‐induced imbalance in the titer of ecdysteroid and juvenile hormone could make great contributions to the abnormal development in reproductive system and have influences on reproduction via impairment of oogenesis and vitellogenesis, reducing mating probability and motility . In this study, the effect of azadirachtin on the reproduction in male S.litura was recorded, and iTRAQ combined with molecular evidence was applied to isolate the azadirachtin‐responsive proteins in male reproductive organ of S.litura to uncover the detailed mechanism.…”
Section: Discussionmentioning
confidence: 83%
“…Previously, azadirachtin was reported to impair, with variable effects, the survival of different insect species . Strong variations in insects' susceptibility to azadirachtin were noted depending on insect order, species, formulation, or the method of application . Sensitivity of insects to insecticides varies also with the regulation of plasma membrane receptor and/or ion channels, penetration rate through the cuticle, absorption by insects, transport in tissues of the body and metabolism …”
Section: Discussionmentioning
confidence: 99%
“…Studies have reported various effects of neem products on non‐target species, such as mites, parasitoids and bees . For example, behaviour and morphological alterations have been highlighted in bees, while Bernades et al . did not detect any effect on worker bee mortality, flight, or respiration rate.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…L'azadirachtine agit en effet comme un régulateur de croissance, ou perturbateur du développement (comme les agonistes ou antagonistes des ecdystéroïdes et de l'hormone juvénile) [6,7]. Un impact de ce type de produits sur les arthropodes utiles n'est donc pas à écarter [33] et plusieurs études, bien que controversées, ont révélé la toxicité des produits issus du margousier sur des espèces non visées [34][35][36][37]. Ainsi, chez les abeilles, des altérations comportementales et morphologiques ont été observées chez les individus soumis à l'azadirachtine, mais aucun effet sur la viabilité (pour les abeilles ouvrières), le vol ou sur la respiration n'a été mis en évidence [36,37].…”
Section: Revues … Et Les Organismes Non Visésunclassified